PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI DI BADAN PENGEMBANGAN SUMBER DAYA MANUSIA (BPSDM) ACEH - Sultan Dandi; Nadiya; Agus Ariyanto (An Nuqud Journal of Islamic Economics, 2025)
The purpose of this study is to determine the influence of leadership style and motivation on employee performance at the Aceh Human Resources Development Agency (BPSDM). The object of this study is leadership style and motivation on employee performance at the Aceh Human Resources Development Agency (BPSDM). The sample size for this study was 63 respondents. Data were collected through questionnaires and documentation studies. The data analysis in this study used multiple linear regression analysis, the F-test, and the t-test to simultaneously and partially determine the effect of the independent variables on the dependent variable at a 95% confidence level 0.05. The results of the partial test showed that the variables of leadership style and motivation significantly influenced employee performance at the Aceh Human Resources Development Agency (BPSDM). Furthermore, the results of the simultaneous test showed that the variables of leadership style and motivation significantly influenced employee performance at the Aceh Human Resources Development Agency (BPSDM).